Productivity and Water Use by Rain-Fed Early Maturing Cassava (Manihot Esculenta Crantz) Varieties Grown at Different Plant Densities in a Coastal Savannah Environment - Amanor, E.N. (University of Ghana, 2016)
The production of cassava (Manihot esculenta Crantz) under rain-fed conditions at the Kwabenya-Atomic area in the coastal savannah environment is constrained by low and erratic rainfall events. Improving cassava production in the area requires the use of cassava varieties which are efficient in the use of limited soil moisture. The objective of the study was to evaluate the response of two early maturing cassava varieties to three (3) planting densities to TDM, RY, and WUE. The actual evapotranspiration was also partitioned into crop transpiration and soil evaporation using LAI data. The field experiment was conducted at Biotechnology and Nuclear Agriculture Research Institute (BNARI) research farm, Atomic Energy Commission (GAEC), Kwabenya-Atomic in 2015. The split plot design in three replicates was used. The two (2) cassava varieties, Bankye Hemaa and Capevars Bankye, were assigned to the main plots and three (3) planting densities: 10,000, 13,333 and 20,000 plants ha-1 to the subplots. Plants were sampled each month and moisture in the 120 cm soil profile monitored every two weeks using the neutron probe (CPN 503 Hydroprobe). Soil moisture data were used to estimate actual evapotranspiration (AET) using the water balance approach. Root yield (RY) for Bankye Hemaa and Capevars Bankye, ranged from 2.8 to 15.1 t/ha-1 for the 10,000 plants ha-1, 4.2 to 18.1 t/ha-1 for the 13,333 plants ha-1 and 5.1 to 21.3 t/ha-1 for the 20,000 plants ha-1. Additionally, water use efficiency in term of total dry matter (WUETDM ) for the two cassava varieties ranged from 1.7 to 11.6, 2.3 to 12.8 and 3.7 to 12.4 kg ha-1 mm-1 for the 10,000, 13,333 and 20,000 plants ha-1 planting density, respectively. Bankye Hemaa grown at 20,000 plants ha-1 produced the highest root yield of 21.3 t/ha-1 and WUETDM of 12.4 kg ha-1 mm-1, because of the comparatively lower soil evaporation which led to increased available soil water for crop use and higher crop transpiration, leading to enhanced yield and water use efficiency. A good positive correlation existed between TUERY and RY for both cassava varieties grown at the planting density of 20,000 plants ha -1 with Bankye Hemaa producing a near perfect linear relation (TUERY = 0.0011RY + 13.492, r2 = 0.97; P ≤ 0.01**). Additionally, a linear model sufficiently describes the relation between the combined total dry matter (TDM) and its associated water use efficiency for Bankye Hemaa and Capevars Bankye grown at all three planting densities: 10,000 plants ha-1 (WUETDM = 0.0011TDM + 1.4628, r2 = 0.90; P ≤ 0.01**) , 13,333 plants ha-1 (WUETDM = 0.0012TDM + 2.8, r2 = 0.90; P ≤ 0.01**) and 20,000 plants ha-1 (WUETDM = 0.0001TDM + 2.6754, r2 = 0.90; P ≤ 0.01**) . Furthermore, a strong and positive correlation existed between WUERY and RY for both cassava varieties grown at all three planting densities: 10,000 plants ha -1 (WUERY = 0.0012RY + 3.1252, r2 = 0.94; P ≤ 0.01**), 13,333 plants ha -1 (WUERY = 0.001RY + 4.052, r2 = 0.92; P ≤ 0.01**) and 20,000 plants ha -1 (WUERY = 0.001RY + 4.7749, r2 = 0.97; P ≤ 0.01**).